1993
DOI: 10.1083/jcb.122.3.541
|View full text |Cite
|
Sign up to set email alerts
|

Tail-specific antibodies that block return of 46,000 M(r) mannose 6-phosphate receptor to the trans-Golgi network

Abstract: Abstract. Recycling of 46,000 Mr mannose 6-phosphate receptor (MPR 46) was investigated by microinjection of Fab fragments against small epitopes within the cytoplasmic domain of the receptor. Fab fragments against the peptide 43-47 (Ala-Tyr-Arg-Gly-Val) efticiently blocked return of MPR 46 to the TGN. Antibody-induced redistribution resulted in accumulation of MPR 46 within an endosomal compartment, from which it recycled to the plasma membrane. Rab5 and rab7, markers for early and late endosomes, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…It has been shown that microinjection of a short MPR46 tail peptide comprising the dileucine signal leads to missorting of MPR46 into an endosomal compartment and to a block in the return of the receptor to the TGN (31). Consistent with this observation the ultrastructural and biochemical data presented here show the importance of the dileucine motif for endosomal sorting of MPR46.…”
Section: The Dileucine Motif As a Determinant For Endosomal Sorting Osupporting
confidence: 87%
“…It has been shown that microinjection of a short MPR46 tail peptide comprising the dileucine signal leads to missorting of MPR46 into an endosomal compartment and to a block in the return of the receptor to the TGN (31). Consistent with this observation the ultrastructural and biochemical data presented here show the importance of the dileucine motif for endosomal sorting of MPR46.…”
Section: The Dileucine Motif As a Determinant For Endosomal Sorting Osupporting
confidence: 87%
“…Our results, therefore, indicate that although the exit of CI-MPR from the endocytic pathway toward the TGN seems to be perturbed by dynK44A overexpression, the CI-MPR is not missorted to lysosomes but accumulates in a prelysosomal compartment. Similarly, Schulze-Garg et al (1993) reported that, after injection of specific antibodies against its cytoplasmic tail, the CD-MPR (the 46-kDa MPR) redistributed to an intermediate compartment on the endocytic pathway in which the receptor segregated from materials destined to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some support for this notion has come from the study of Green et al (1994) that demonstrated that P-selectin contains a signal in its cytoplasmic tail that is necessary for efficient delivery to lysosomes. In contrast, experiments with microinjected antibodies specific for the cytoplasmic tail of the CD-MPR have led to the suggestion that recycling from endosomes to the Golgi complex is signal mediated (Schulze-Garg et al, 1993). Consistent with this view, an immunoelectron microscopy study of HepG2 and BHK cells revealed that the CD-MPR and the asialoglycoprotein receptor are sequestered into separate tubular-vesicular structures associated with endosomes (Klumpermann et al, 1993).…”
mentioning
confidence: 99%